Strategy for Creating an Effective Needs Analysis to Improve PAI Learning Quality - Siti Rohmah Kurniasih; Mulyawan Safwandy Nugraha (Zona Education Indonesia, 2023)
The quality of PAI learning shows low results. This is because PAI learning in schools still uses conventional methods with a classical approach, so it does not pay attention to students' learning needs. Besides, PAI teachers are less aware of the importance of designing a needs analysis before the learning process so that it has an impact on not achieving objectives. optimal learning. This research aims to explain the urgency and strategy of designing needs analysis in PAI learning. The method used is a qualitative research method using a case study approach. The required data sources come from primary data sources, namely the results of interviews with PAI teachers at SDN Dayeuhkolot 03, and secondary data sources from books, articles, and scientific journals. Data collection techniques include observation and interviews. Meanwhile, data analysis uses a triangulation approach. The research results show that designing a needs analysis is important to improve the quality of PAI learning. Apart from that, it is hoped that the results of this research can provide an overview to PAI teachers regarding strategies for designing effective needs analyses.